Development of Problem-Based Learning Teaching Materials on Heat and Temperature to Improve High School Students' Critical and Creative Thinking Skills - Sukandar, Sukandar; Rusilowati, Ani; Wahyudin, Agus (Universitas Negeri Semarang, 2025)
Critical and creative thinking skills are part of the High-Order Thinking Skills required by the Independent Curriculum and 21st century education. It is hoped that students will be able to analyze, evaluate, and create creative solutions in learning, especially in science subjects at the high school level. The purpose of this study is to produce problem-based learning tools on temperature and heat materials to improve the critical and creative thinking skills of valid high school students, to find out the practicality and effectiveness of problem-based learning tools on temperature and heat materials to improve the critical thinking and creative thinking skills of high school students. This research is development research. Data collection through tests, observations, questionnaires and documentation. The development model used is 3-D (Define, Design, Develop) which includes the stages of definition, design, and development. The tools developed consist of syllabuses, lesson plans, worksheets, student teaching materials, and learning outcome tests. The trial was carried out at SMA Negeri 1 Kudus in the experimental class and the control class. Validation by three validators showed an average score: 3.51 syllabus; Learning Implementation Plan 3.73; student worksheet 3.73; Student Achievement 3.54; Critical Thinking Observation Sheet 3.71; and creativity 3.67 out of a maximum score of 4. The learning outcome test is declared valid, balanced in difficulty, well distinguished, and reliable. Practicality is shown from the teacher's response (average 4.60) and the teacher's ability to manage learning (average 4.59). Effectiveness was shown by an increase in the learning outcomes of experimental students, critical thinking skills by 79%, and creativity by 54%. These devices are proven to be valid, practical, and effective.